Angels of God: the Bible, the church, and the heavenly hosts - Aquilina, Mike (Servant Books, 2009)
Introduction: The everywhere of angels -- What is an angel? -- The testing of angels -- Angels in the Old Testament -- Angels in the New Testament -- The kinds of angels -- Guardian angels -- The angels at worship -- Michael, our defender -- Gabriel, the great communicator -- Raphael, friend and guide -- Spiritual warfare -- The angels and us